2013
DOI: 10.1620/tjem.229.195
|View full text |Cite
|
Sign up to set email alerts
|

D-Ribose Ameliorates Cisplatin-Induced Nephrotoxicity by Inhibiting Renal Inflammation in Mice

Abstract: Cisplatin is one of the most potent chemotherapeutic anticancer drugs, but it can produce side effects such as nephrotoxicity. Inflammatory cytokines, chemokines and adhesion molecules have important roles in the pathogenesis of cisplatin-induced nephrotoxicity. D-Ribose is a naturally occurring five-carbon monosaccharide that is found in all living cells, and has anti-inflammatory effects in renal ischemia/ reperfusion injury. The purpose of this study was to determine the protective effects of D-ribose on ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 24 publications
(47 reference statements)
3
15
0
Order By: Relevance
“…Infiltration of damaged renal tissue with inflammatory cells is characteristic for CDDP-induced nephrotoxicity. 20 Our experiment showed a significant elevation of renal TNF-a and MCP-1 gene expressions in CDDP group when compared to the normal group and this findings is in accordance with the study of Ueki et al 20 who reported a significant elevation of renal TNF-a and MCP-1 after CDDP injection.…”
Section: 17supporting
confidence: 91%
See 3 more Smart Citations
“…Infiltration of damaged renal tissue with inflammatory cells is characteristic for CDDP-induced nephrotoxicity. 20 Our experiment showed a significant elevation of renal TNF-a and MCP-1 gene expressions in CDDP group when compared to the normal group and this findings is in accordance with the study of Ueki et al 20 who reported a significant elevation of renal TNF-a and MCP-1 after CDDP injection.…”
Section: 17supporting
confidence: 91%
“…18,19 Concerning inflammation, it was reported that TNF-a is a proinflammatory cytokine that acts as an important mediator of CDDP-induced inflammatory tissue damage. 20 It is able to induce direct renal injury and causes induction of apoptosis and necrotic cell death. 21 TNF-a also stimulates the release of other cytokines and chemokines, such as MCP-1, 22 which attracts a variety of cells including leukocytes, monocytes and natural killer cells.…”
Section: 17mentioning
confidence: 99%
See 2 more Smart Citations
“…A single dose of CP caused apoptosis in kidney. It seems that inflammatory responses with regard to the weight of animals are acute consequence of CIS administration that occurs during 3-4 days after exposure (Ueki et al, 2013). In vivo administration of nephrotoxic doses of CP produces a large increase in apoptosis in the kidney (Ramesh & Reeves, 2004).…”
Section: Discussionmentioning
confidence: 99%